PENILAIAN PENGUNJUNG TERHADAP PENGELOLAAN FASILITAS PADA OBJEK WISATA AIR PANAS HAPANASAN KABUPATEN ROKAN HULU - Sinta "; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
In Indonesia, the tourism sector is currently growing faster, the tourism sector is a potential that is developed to be a source of income. Riau is one of the tourist destinations that is quite interesting, such as Rokan Hulu Regency which has tourism potential of natural wealth which makes a tourist attraction, namely Hapanasan hot water which is a superior tourist spot in Rokan Hulu Regency, with that the author takes the title of visitor assessment of facility management at Tourist attraction Air Panas Hapanasan Rokan Hulu which aims to determine the responses of visitors who visit the object air panas hapanasan regarding facilities in tourist objects, the researcher uses Spillane's theory (1994), which says that the facility is a means of supporting daily operational tourism objects. To accommodate the needs of visitors, it indirectly supports growth but develops at the same time after the attraction of this research is carried out at air panas hapanasan , Rokan Hulu Regency, this research was conducted for 4 months, starting from March to June 2020. This research is a quantitative research, the data collection technique uses observation questionnaire techniques, and documentation. The sample of the research is visitors. The results of this recapitulation show that overall the respondents gave good responses to the facilities at the air panas hapanasan tourism object.  Keywords: Assessment, Management, Facilities, Tourism and Attration.